Effects of in Season Multi-Directional Plyometric Training on Vertical Jump Performance, Change of Direction Speed and Dynamic Postural Control in U-21 Soccer Players - Jlid, Mohamed Chedly; Coquart, Jérémy; Maffulli, Nicola; Paillard, Thierry; Bisciotti, Gian Nicola; Chamari, Karim (Frontiers in Physiology, 2020)
The aim of the study was to assess the effects of multi-directional plyometric training (MPT) on vertical jump height, change of direction speed (CODS) and dynamic postural control (DPC) of soccer players under 21 year (U-21). Twenty-seven male soccer players were randomly allocated to either an experimental group (EG; n = 14; age: 19.0 ± 0.9 years) or a control group (CG; n = 13; age: 19.0 ± 0.7 years). The EG introduced 6 weeks MPT, two days per week into their in-season training, while CG continued training without change. Measurements of vertical jump height, CODS and DPC were completed at the beginning and end of the 6 week MPT. ANOVA demonstrated a significant group × time interaction for SJ (F=6.03, p=0.021), CMJ (F=9.10, p=0.006) and T-Test (F=10.46, p=0.002). The Bonferroni Post Hoc test demonstrated significant increase for the three tests in both group (EG and CG). For SJ (EG: p<0.001; CG: p<0.001), CMJ (EG: p<0.001; CG: p=0.005) and T-Test (EG: p<0.001; CG: p=0.02). For DPC on the dominant leg, there was a significant group × time interaction for four axes [anterior (F=5.48, p=0.028), antero-lateral (F=4.82, p=0.038), postero-lateral (F=4.82, p=0.038) and medial (F=6.77, p=0.015)]. The Bonferroni Post Hoc test demonstrated significant increase in EG (p<0.001), but no significant change in CG in four axes (anterior, antero-lateral, postero-lateral and medial). Furthermore DPC on the non-dominant leg, there was a significant group × time interaction for three axes [lateral (F=8.09, p=0.009), postero-lateral (F=11.92, p=0.002) and medial (F=5.84, p=0.023)]. The Bonferroni Post Hoc test demonstrated significant increase in EG (p<0.001), but no significant change in CG in three axes (lateral, postero-lateral and medial).In conclusion, incorporating MPT into the in-season regimen of under 21 soccer players improved performance of various indices related to soccer activity (i.e., CMJ, CODS and DPC). MPT has the potential to be appealing to coaches, as it requires little time while yielding valuable results in the physical preparation of soccer players.